(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A Inverted Umbrella Roof Shell, treated from the Analytical based software in ANSYS and Statistically aspects, is a analyzed in this paper. In the Analytical sense, it is the solid shell of a great frequency and wide usability in a spatial structures, either as the complete form or in the parts. In the statistically regression analysis on graphs results sense, it is treated on the graphically results on which it is possible to the determine the exacts frequency on at each modes and field of the infinitesimal maximum deformations, and it is rigid by using Ferrocement.